United States : Financial Sector Assessment Program-Technical Note-Supervision of Financial Market Infrastructures, Resilience of Central Counterparties and Innovative Technologies. (IMF Staff Country Reports; Country Report ;, 2020)
The Unites States financial system includes several systemically important financial market infrastructures (FMIs); they are regulated, supervised, and overseen by multiple authorities. The U.S. FMIs are crucial to U.S. dollar clearing, id est the payment systems Fedwire Funds Service and The Clearing House Interbank Payments System (CHIPS), and for the clearing and settlement of U.S. Treasuries, id est, the Fedwire Securities Service and the Fixed Income Clearing Corporation (FICC). Central counterparties (CCPs) that clear exchange-traded or over-the-counter (OTC) corporate securities or derivatives are of key importance to the safe and efficient functioning of these (global) markets. Disruption of critical operations at one of the large U.S. FMIs may spread to its participants, other FMIs, markets, and throughout the U.S. and global financial systems. The Financial Stability Oversight Council (FSOC) designated eight financial market utilities (FMUs) to be systemically important.1 These designated FMUs are regulated, supervised and overseen by the Federal Reserve Board (FRB), the Securities and Exchange Commission (SEC), or the Commodity Futures Trading Commission (CFTC), depending on their activities. In addition, the Dodd-Frank Wall Street Reform and Consumer Protection Act (DFA) authorized the FRB to promote uniform standards for the management of risks by systemically important FMUs.